2000
DOI: 10.1002/(sici)1099-0720(200001)14:1<19::aid-acp619>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing learning through strategy instruction and group interaction: is active generation of elaborations critical?

Abstract: We examined strategic intervention when learners were actively engaged in group discussion to assess the impact of peer interaction. In addition, memory performance was compared between students who generated or evaluated elaborations when using the elaborative interrogation strategy, as well as between a supported strategy where learners were provided with explanatory elaborations and a self‐study condition. Introductory psychology students (N=263) in groups of 3 to 5 members studied sixty facts about familia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 25 publications
1
23
0
Order By: Relevance
“…They consider the role of elaboration more important than other types of information processing. Substantial evidence in experimental research (e.g., King, 1992;Willoughby, Wood, McDermott, & McLaren, 2000) and survey research (e.g., Eveland et al, 2004;Miller, Always, & McKinley, 1987) has demonstrated that elaboration facilitates learning. This study hypothesizes that immediacy gratification predict news elaboration.…”
Section: Discussionsupporting
confidence: 47%
“…They consider the role of elaboration more important than other types of information processing. Substantial evidence in experimental research (e.g., King, 1992;Willoughby, Wood, McDermott, & McLaren, 2000) and survey research (e.g., Eveland et al, 2004;Miller, Always, & McKinley, 1987) has demonstrated that elaboration facilitates learning. This study hypothesizes that immediacy gratification predict news elaboration.…”
Section: Discussionsupporting
confidence: 47%
“…However, prior research supporting that learning can be facilitated by EI even when prior knowledge is low has focused primarily on learners engaged in studying sentences (Symons and Greene 1993;Woloshyn et al 1992). Thus, in general, while EI has proven to be most effective when learners' repertoires include a rich knowledge base (Willoughby et al , 2000(Willoughby et al , 2003, in situations where prior knowledge is low Willoughby et al 2003) or when studying unfamiliar domains (Symons and Greene 1993;Woloshyn et al 1992), EI has facilitated performance minimally at best. Results from the current investigations support findings from previous studies that indicate only learners with relevant knowledge benefit from using the EI strategy (Willoughby et al 1993Wood et al 1990).…”
Section: Levels Of Elaboration and Utility Of Strategiesmentioning
confidence: 99%
“…However, research indicates that children and adults respond differently to the same type of content when they are asked to think about information compared with when they are told that information. Research has shown consistently that asking questions enhances learning among both adults (Pressley, et al, 1992;Willoughby, Wood, & Khan, 1994;Willoughby, Wood, McDermott, & McLaren, 2000;Zillmann & Cantor, 1973) and older children (Wood, Pressley, & Winne, 1990;Wood, Willoughby, Bolger, Younger, & Kaspar, 1993).…”
Section: Mediation Formmentioning
confidence: 99%